Experience in the treatment of a primary infected kidney transplant - M. Sh. Khubutiya; D. V. Lonshakov; A. G. Balkarov; Yu. A. Anisimov; N. V. Shmarina; N. V. Zagorodnikova; V. O. Aleksandrova; I. V. Dmitriev (Трансплантология (Москва))
Introduction. Infectious complications contribute to a significant decrease in graft and recipient survival rates. The article describes a case report of transplantation of the primary infected kidney transplant. Material and methods. A 33-year-old patient with type 1 diabetes mellitus and end-stage renal disease underwent kidney transplantation. The deceased donor was a 46-year-old man with a confirmed brain death as a result of acute cerebrovascular accident. Results. The early postoperative period was complicated by the development of primary infection of kidney transplant. Despite the ongoing treatment aimed at preserving the transplant, we had to remove it in order to prevent the development of further complications. Conclusion. Kidney transplantation improves the quality of life of patients with end-stage renal disease. In case of uncontrolled course of the infectious process after primary infected graft transplantation, it is necessary to perform transplantectomy in a timely manner in order to save the recipient’s life, since the graft itself is the source of infection.